2010
DOI: 10.1007/s13197-010-0151-9
|View full text |Cite
|
Sign up to set email alerts
|

Processing and storage of Indian cereal and cereal products alters its resistant starch content

Abstract: Resistant Starch (RS) is prebiotic in nature and is defined as the sum of starch and products of starch degradation not absorbed in small intestine of healthy individuals but later are fermented by natural microflora of the colon to produce short chain fatty acids. RS acts as a nutraceutical and its consumption leads to many health benefits. The aim of the study is to analyze the RS content in raw and processed cereals and cereal products and determine various processing and storage effects on the RS content. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
21
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 15 publications
6
21
1
1
Order By: Relevance
“…Significant increase in RS content by 1.3, 1.5 and 1.7 fold in maize rotla, chapatti and pearl millet rotla respectively, was also observed by Vaidya et al 28 .…”
Section: Resultssupporting
confidence: 71%
See 3 more Smart Citations
“…Significant increase in RS content by 1.3, 1.5 and 1.7 fold in maize rotla, chapatti and pearl millet rotla respectively, was also observed by Vaidya et al 28 .…”
Section: Resultssupporting
confidence: 71%
“…The RS value for Paratha was significantly higher than Chapatti and Puri (P>0.05), whereas the difference between the RS content of Paratha and Bhatura was not statistically significant (P>0.05). Increase in RS value in shallow fried preparations has been reported in a study 28 in which shallow fried Paratha showed a non-significant increase in RS value as compared to raw wheat flour, whereas Thepla made out of pearl millet showed significantly higher RS value than raw pearl millet.…”
Section: B S Yadavsupporting
confidence: 56%
See 2 more Smart Citations
“…This is may be attributed to that soaking in hot water and pressure cooking causes significant increase in starch digestibility [49], where the starch gelatinization has taken place, accompanied with molecular breakdown resulted in higher exposure of the starch fractions to the digestive enzymes [19], and with the increase in the degree of parboiling, the digestibility increased [46]. The reason for lesser digestibility shown by popped rice paper, probably due to that tempering in salt, followed by popping with hot air convection, helped in formation of resistance starch [50]. This resistant form of starch is considered dietary starch, that resist the digestion and give lesser digestibility than dry roast parboiling treatment [51].…”
Section: In Vitro Starch Digestibility Of Broken Rice Flour and Untrementioning
confidence: 99%